Representations (and dissemination) of sexuality. Lea Lublin amid local censorship and international circulation - Isabel Plante (Nuevo mundo - Mundos Nuevos, 2017)
This article focuses on two works by Lea Lublin that address sexuality and the restrictions for the public exhibition of erotic representations: Blanco sobre blanco (White on white, 1969) and Lecture d’une œuvre de Lea Lublin par un inspecteur de police (Reading of a Lea Lublin’s work by a police inspector, 1972). While the first was created and exhibited in Buenos Aires, the second was, by contrast, produced and presented in Paris. We argue that the censorship of Blanco sobre blanco confirmed the relevance of the artist’s interest in investigating the nature of representation as a visual device and the exploring the links of images with institutions, the imaginary and the libidinal. The esthetic connection of her trajectory as a migrant artist allowed her to strategically use the political and institutional asymmetries between both metropolises: Paris became a city where she could critically visualize and address the effects of the control of the Argentine dictatorship under General Juan Carlos Onganía (1966-1970) on sexuality and its representations.